THE GREEN PORTS FUTURE KNOWLEDGE MAP AND TREND - Nurdin Ahmadi; Sri Rahardjo; Sinta Hasriningtyas (Coastal and Ocean Journal (COJ), 2023)
The purpose of this study is to track the emergence of research related to green ports over time and determine the knowledge map and trends of green port research topics in the future using thematic map bibliometric analysis. This study also provides an overview of the researchers and contributors of research countries in green port research globally. This research provides a comprehensive bibliometric analysis of historical developments and current trends in green port research, by examining 462 articles published from 1991-2023 on the Scopus database. This research uses R studio Cloud bibliometric analysis and biblioshiny package. It was found that there are three phases in green port research, namely the initial stagnation phase (1991-2006), infant growth (2007-2015), and expanding phase (2016-2022), the number of articles increased quite rapidly in the third phase until now. This research also highlights related to authors, contributor countries and it was found that the country of China contributed the most contributor authors compared to other countries, this is because China is a country that places many container ports as the top 10 largest container ports in the world, with a total market share reaching 70% of the global. From this analysis, it is found that the knowledge map and the direction of future topics related to green ports are “sustainable development”, “port development”, “port operation”, “carbon emissions” and “renewable energy resources”, besides that it is also found that there is a direction of the current green port and “smart port” research trends. So, it can be recommended that in the future these topics will be very relevant to develop, the themes of research themes needed include alternative strategies in net zero emission (NZE) in ports in the operational and development aspects of the port.